Dynamic Regulation of H3K27 Trimethylation during Arabidopsis Differentiation - Lafos, Marcel (Public Library of Science, 2011)
During growth of multicellular organisms, identities of stem cells and differentiated cells need to be maintained. Cell fate is epigenetically controlled by the conserved Polycomb-group (Pc-G) proteins that repress their target genes by catalyzing histone H3 lysine 27 trimethylation (H3K27me3). Although H3K27me3 is associated with mitotically stable gene repression, a large fraction of H3K27me3 target genes are tissue-specifically activated during differentiation processes. However, in plants it is currently unclear whether H3K27me3 is already present in undifferentiated cells and dynamically regulated to permit tissue-specific gene repression or activation. We used whole-genome tiling arrays to identify the H3K27me3 target genes in undifferentiated cells of the shoot apical meristem and in differentiated leaf cells. Hundreds of genes gain or lose H3K27me3 upon differentiation, demonstrating dynamic regulation of an epigenetic modification in plants. H3K27me3 is correlated with gene repression, and its release preferentially results in tissue-specific gene activation, both during differentiation and in Pc-G mutants. We further reveal meristem- and leaf-specific targeting of individual gene families including known but also likely novel regulators of differentiation and stem cell regulation. Interestingly, H3K27me3 directly represses only specific transcription factor families, but indirectly activates others through H3K27me3-mediated silencing of microRNA genes. Furthermore, H3K27me3 targeting of genes involved in biosynthesis, transport, perception, and signal transduction of the phytohormone auxin demonstrates control of an entire signaling pathway. Based on these and previous analyses, we propose that H3K27me3 is one of the major determinants of tissue-specific expression patterns in plants, which restricts expression of its direct targets and promotes gene expression indirectly by repressing miRNA genes.